Remarkably low genetic diversity in the widespread cave spider Phanetta subterranea (Araneae, Linyphiidae) - Kathryn A. Kennedy; Kirk S. Zigler; Brendan Cramphorn; Curt W. Harden; Kurt Helf; Julian J. Lewis; Thomas E. Malabad; Marc A. Milne; Matthew L. Niemiller; Charles D. R. Stephen (Subterranean Biology)
Most cave-obligate species (troglobionts) have small ranges due to limited dispersal ability and the isolated nature of cave habitats. The troglobiontic linyphiid spider Phanetta subterranea (Emerton, 1875), the only member of its genus, is a notable exception to this pattern; it has been reported from more counties and caves than any other troglobiont in North America. As many troglobionts exhibit significant genetic differentiation between populations over even small geographic distances, it has been hypothesized that Phanetta may comprise multiple, genetically distinct lineages. To test this hypothesis, we examined genetic diversity in Phanetta across its range at the mitochondrial cytochrome c oxidase subunit I gene for 47 individuals from 40 caves, distributed across seven states and 37 counties. We found limited genetic differentiation across the species’ range with haplotypes shared by individuals collected up to 600 km apart. Intraspecific nucleotide diversity was 0.006 +/- 0.005 (mean +/- SD), and the maximum genetic p-distance observed between any two individuals was 0.022. These values are within the typical range observed for other spider species. Thus, we found no evidence of cryptic genetic diversity in Phanetta. Our observation of low genetic diversity across such a broad distribution raises the question of how these troglobiontic spiders have managed to disperse so widely.